ELECTROMAGNETIC RADIATION EXPOSURE FROM CELLULAR BASE STATION: A CONCERN FOR PUBLIC HEALTH (Nigerian Journal of Technology, 2015)
For cellular network Base Transceiver Station (BTS) antennas to operate as intended without adverse health effects, they must comply with Electromagnetic Compatibility (EMC) standards as well as safety guidelines relating to exposure of non-ionizing radiation. Global System for Mobile Communication (GSM) operators claimed that their equipment comply with international standards and thus the radiated field propagated from their installation complies with International Commission on Non-Ionizing Radiation Protection (ICNIRP) requirements. However, the installation of GSM BTS might not comply with maximum exposure limit as Nigeria Communication Commission (NCC) does not supervise the installation, therefore, the public and more specifically, the maintenance personnel’s health might be at risk. More worrisome is that investigation has shown that none of the cellular network operators in Nigeria provide quality training for their worker on awareness of occupational radiation hazards from BTS.  This paper call for caution and show how best practice can be followed by general public and maintenance personnel to avoid being exposed to radiation so that their health is not at risk while the uncertainties about the hazard effects last. http://dx.doi.org/10.4314/njt.v34i2.20